2010
DOI: 10.1177/183693911003500404
|View full text |Cite
|
Sign up to set email alerts
|

Children's Transition to School: Voices of Bangladeshi Parents in Sydney, Australia

Abstract: ThE STuDy on WhICh this paper is based explored Bangladeshi parents' perceptions of children's transition to school. The paper reports on the data obtained from interviews with 10 parents living in Sydney, Australia, on their children's experiences when beginning school. According to the parents, friendships with peers who share a similar cultural or linguistic background and support from school teachers facilitated their children's positive adjustments to school, whereas limited or lack of proficiency in Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
2
15
0
1
Order By: Relevance
“…This woman talked about her huge sense of responsibility to her husband's family in raising her daughter according to traditional values, and her desire to evade chastisement from them. Findings in the present study are similar to existing research on migrants (Sanagavarapu, 2010;Sanagavarapu & Perry, 2005) which found that these parents were concerned over children losing their original culture upon exposure to western values in the school environment.…”
Section: Preparing For Schoolsupporting
confidence: 87%
See 1 more Smart Citation
“…This woman talked about her huge sense of responsibility to her husband's family in raising her daughter according to traditional values, and her desire to evade chastisement from them. Findings in the present study are similar to existing research on migrants (Sanagavarapu, 2010;Sanagavarapu & Perry, 2005) which found that these parents were concerned over children losing their original culture upon exposure to western values in the school environment.…”
Section: Preparing For Schoolsupporting
confidence: 87%
“…They suggested this would help teachers to understand different cultures and allow the mothers to learn more about the school system. This finding reflects the views of migrant parents in Sanagavarapu's (2010) study, which also talked about the importance of increased communication and cultural awareness at children's schools.…”
Section: Perceived Supportssupporting
confidence: 74%
“…As noted by Margetts (2013), transition includes preparations conducted in the home, orientation programmes and the initial period of attendance. Most research investigating early years transitions has been conducted utilising the voices of the educators (Hammond, 2009); children's parents (Sanagavarapu, 2010); or a combination of the two. More recently, studies have begun to include the voices of child participants when possible (Clark & Moss, 2011).…”
Section: Transitionmentioning
confidence: 99%
“…Educational transitions are considered major challenges that young children face (Sanagavarapu, 2010), and include the challenge of becoming and being acknowledged as competent in a new and diverse environment. It has been established that successful early educational transitions set the tone for future success and personal wellbeing (Perry et al, 2013).…”
Section: Transitionmentioning
confidence: 99%
“…For example, they need to understand the rules of school, make new friends, learn to play cooperatively with peers, know the facilities and communicate their needs and concerns, learn to relate to their classroom teacher and other adults, and to be independent and self-reliant in a school setting (Perry, Dockett & Howard, 2000). Transition to school is a very complex process for children, and therefore for their families (Perry et al, 2000;Perry, Dockett & Nicholson, 2002;Sanagavarapu & Perry, 2005;Sanagavarapu, 2010).…”
Section: Implications Of Food Allergy For Starting Schoolmentioning
confidence: 99%